Review of "Epistemic Rights in the Era of Digital Disruption": by Minna Aslama Horowitz, Hannu Nieminen, Katja Lehtisaari and Alessandro D’Arma (Eds.) 2024. Palgrave Macmillan. - Molek-Kozakowska, Katarzyna (Władza Sądzenia, 2024)
This review essay summarizes and evaluates the merits of individual chapters in the collection entitled Epistemic Rights in the Era of Digital Disruption, a recent publication in Palgrave’s International Association for Media and Communications Research series. The reviewer offers an overview of the current understanding of the concept of “epistemic rights”, explains how the book portrays the disruptive context of recent digital transformation of the public sphere, and echoes the call articulated by the editors and authors in the collection to strengthen democracies by acknowledging citizens’ epistemic rights as part of larger extension of human rights in the mediatized societies.